2007
DOI: 10.1002/ceat.200600357
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Displacement of Yoghurt by Water in a Pipe Using CFD

Abstract: A numerical scheme based on the volume of fluid (VOF) method for predicting the displacement of one liquid by another has been verified versus electrical resistance tomography (ERT) and ultrasonic velocity profile (UVP) measurements for the displacement of yoghurt by water. The scheme using the VOF method predicts the skewed phase distribution as measured using ERT and the global structure of the velocity profile as measured using UVP. The phase distribution using the VOF method was compared with the results u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…As a consequence, there have been several recent studies which have investigated this aspect in various systems, such as porous media, 23 chemically driven systems, [24][25][26][27][28][29] and also in food processing industries and diary plants. 30 The instabilities which arise due to viscosity stratification in different geometries, such as in miscible channel flows and core-annular miscible flows are well documented in literature, and discussed in a recent review by Govindarajan and Sahu. 31 The articles relevant to the present study have examined flow system in a rigid channel (the linear stability analysis of SC systems; 11,22,[32][33][34][35][36] convective and absolute instabilities in SC systems 37 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, there have been several recent studies which have investigated this aspect in various systems, such as porous media, 23 chemically driven systems, [24][25][26][27][28][29] and also in food processing industries and diary plants. 30 The instabilities which arise due to viscosity stratification in different geometries, such as in miscible channel flows and core-annular miscible flows are well documented in literature, and discussed in a recent review by Govindarajan and Sahu. 31 The articles relevant to the present study have examined flow system in a rigid channel (the linear stability analysis of SC systems; 11,22,[32][33][34][35][36] convective and absolute instabilities in SC systems 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sahu et al 37 showed that the above system becomes absolutely unstable for a certain range of parameters and have indicated the region of absolute and convective instabilities in the Reynolds number and viscosity ratio space. There are also several investigations 29,30,[38][39][40][41][42][43][44][45][46][47][48] not relevant to the present study (but worth mentioning in the present context) that deals with stability characteristics of viscosity stratified flows in rigid channels/pipes, involving the displacement of one fluid by another. The interesting features and the type of instabilities displayed by these flow systems with boundaries as either rigid walls or rigid circular pipes suggest that it is worth analyzing the analogous flow systems in configurations with velocity slip at the boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The cleaning of plants also involves the removal of viscous fluids by fast-flowing water streams. 2 In enhanced oil recovery, hydrocarbon solvent or supercritical carbon dioxide is used to displace oil from an oil reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…In the food and drink industry, cleaning of plants, involves the removal of a highly viscous fluid by fast-flowing water pumped through the plant. In dairy plants, flows involving these displacements are used during plant start-up and rinsing [3]. Achieving fundamental understanding of these flows in the latter context is important in order to determine the degree of mixing between the fluids and to minimize the amount of waste-water utilized.…”
Section: Introductionmentioning
confidence: 99%